Sustainable Shear Behaviour of 2-Span Continuous Reinforced Concrete T-Beams with CFRP Strips - Abdul Samad Abdul Aziz; Alferjani Marwan B.S.; Ali Noorwirdawati; Mohamad Noridah; Ahmad Mohd Hilton; Tee Kong Fah; Mendis Priyan (MATEC Web of Conferences, 2017)
Reinforced concrete (RC) structures are generally subjected to various load conditions and are susceptible to environmental impact. With time, most of these structures will be subjected to change in their usage. Unexpected increase in load changes may cause severe damage to the structural components, and eventual leading to various types of structural failure. It is noted that shear failure in nature is a sudden failure and should be avoided at all times. To increase its service life due to shear, structures can be strengthened or repaired using CFRP strips wrapped within the shear span (av) of the beam. Hence, this paper presents an investigation on the sustainable behaviour of two span continuous RC T-beams strengthened and repaired by wrapping Carbon Fibre Reinforced Polymer (CFRP) strips at intervals along the shear span (av) of the beam. The CFRP strips will be orientated in two directions either at 0°/90° or 45°/35°. Five beams, one control beam, two initially strengthened beams and two precracked and repaired beams were cast and cured in room temperature before testing. All T-beams were designed to fail in shear and are subjected to four-point bending test until failure. Upon completion of the test, all beam specimens shows good sustainable behaviour as the ultimate load and shear load shows an increase in capacity by up to 23% with improve ductile behaviour.